1982
DOI: 10.1007/bf00239567
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellotectal projections studied in cats with horseradish peroxidase or tritiated amino acids axonal transport

Abstract: After injections of horseradish peroxidase (HRP) into various parts of the superior colliculus (SC) in 14 cats, retrogradely labeled neurons were found in parts of all deep cerebellar nuclei. The present study demonstrated that there are three main origins of the cerebellotectal projections in regard to the locations of the cell bodies: (1) the caudal half approximately of the fastigial nucleus (NM) including the subnucleus medialis parvocellularis (SMP), (2) the ventral and lateral parts of the posterior inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…New World monkeys, too, show a similar two-channel cerebello-tectal projection (Gonzalo-Ruiz et al, 1988), suggesting that all primates are similar in this respect. The cat also possesses a fastigio-tectal bilateral pathway, although there is much more in the way of a caudal overlap with the contralaterally projecting interpositus and dentate projection (Hirai et al, 1982). The results so far discussed and the findings of degeneration studies in the opossum (Martin et al, 1974) and hedgehog (Earle and Matzke, 1974) all point to a possible generalization on the basis of eye position and importance of eye-in-head movements.…”
Section: Other Speciesmentioning
confidence: 83%
“…New World monkeys, too, show a similar two-channel cerebello-tectal projection (Gonzalo-Ruiz et al, 1988), suggesting that all primates are similar in this respect. The cat also possesses a fastigio-tectal bilateral pathway, although there is much more in the way of a caudal overlap with the contralaterally projecting interpositus and dentate projection (Hirai et al, 1982). The results so far discussed and the findings of degeneration studies in the opossum (Martin et al, 1974) and hedgehog (Earle and Matzke, 1974) all point to a possible generalization on the basis of eye position and importance of eye-in-head movements.…”
Section: Other Speciesmentioning
confidence: 83%
“…The intralaminar nuclei are known to receive projections from the nucleus interpositus and the lateral nucleus of the cerebellum (Sugimoto et al, 1981;Hirai et al, 1982;Kawamura et al, 1982), and were reported to play a role in eye movement signal processing (Schlag-Rey and Schlag, 1977). It is also well known that the intralaminar nuclei receive projections from the intermediate layer of SC (Graham, 1977).…”
Section: Connectional and Physiological Consideration Of Each Divisiomentioning
confidence: 98%
“…All cerebellar nuclei also target the neocortex via thalamic innervation. Connectivity based on Hirai et al (1982), Ito (1984), Gibson et al (1987), Zwergal et al (2009) and Bostan et al (2013). Targeted motor structures in turn overlap in their innervation of the spinal interneuronal motor circuitry (Jankowska, 1992;Bortoff & Strick, 1993;Hultborn, 2001;Hammar et al 2011;Jankowska et al 2011a;Shrestha et al 2012;Spanne & Jörntell, 2013).…”
Section: Figure 1 Schematic Illustration Of the Cerebellar Sagittal mentioning
confidence: 99%